PENERAPAN MEDIA PEMBELAJARAN EMAZE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN INFORMATIKA DI SMK NEGERI 1 KUNINGAN - Rama Ubaidillah. M; Yoyo Zakaria (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The selection of appropriate learning media plays an important role in improving student learning outcomes, particularly in Informatics subjects. This study aimed to determine the effect of applying the Emaze learning media on student learning outcomes in Informatics at SMK Negeri 1 Kuningan. This research used a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. The sample consisted of two classes: class XI TKR 1 as the experimental group (30 students) using Emaze, and class XI TKR 2 as the control group (32 students) using conventional learning media, selected through purposive sampling. Data were collected through tests, questionnaires, observation, and documentation, and analyzed using descriptive statistics, normality tests (Shapiro-Wilk), homogeneity tests (Levene), and the Paired Sample t-Test with SPSS. The results showed that the mean posttest score of the experimental class (79.67) was higher than that of the control class (70.94), with an increase of 27.00 points in the experimental class compared to 25.00 points in the control class. The Paired Sample t-Test showed a significance value of 0.000 (p < 0.05) for both classes, indicating a significant difference between pretest and posttest results. Furthermore, the student response questionnaire showed a positive response toward the use of Emaze, with a percentage of 78.2%. It is concluded that the application of the Emaze learning media has a positive effect on improving student learning outcomes in the Informatics subject.